Bioenergy crops, biodiversity and ecosystem services in temperate agricultural landscapes—A review of synergies and trade‐offs - Josefin Winberg; Henrik G. Smith; Johan Ekroos (GCB Bioenergy, 2023)
Abstract The Paris agreement on climate change requires rapid reductions in greenhouse gas emissions. One important mitigation strategy, at least in the intermediate future, is the substitution of fossil fuels with bioenergy. However, using agriculture‐ and forest‐derived biomass for energy has sparked controversy regarding both the climate mitigation potential and conflicts with biodiversity conservation. The urgency of the climate crisis calls for using forests for carbon sequestration and storage rather than for bioenergy, making agricultural biomass an attractive alternative for fossil energy substitution. However, this calls for comprehensive assessments of its sustainability in terms of consequences for biodiversity and ecosystem services. In this review, we provide a first holistic overview of the impacts on ecosystems of land‐use changes from bioenergy crop production in temperate climates, by synthesizing results on both biodiversity and ecosystem service impacts. We found that bioenergy‐related land‐use changes can have both positive and negative effects on ecosystems, with original land use, bioenergy crop type and scale of bioenergy production being important moderators of impacts. Despite the risk of opportunity cost for food production, perennial crop cultivation on arable land had the lowest occurrence of negative impacts on biodiversity and ecosystem services. Growing biomass for bioenergy on surplus land has been suggested as a way to alleviate competition with food production and biodiversity conservation, but our results demonstrate that utilizing marginal or abandoned land for bioenergy crop production cannot fully resolve these trade‐offs. Furthermore, there is a lack of empirical studies of the biodiversity value of marginal and abandoned land, limiting our understanding of the sustainability implications of biomass cultivation on surplus land. We argue that future research and policies for bioenergy production must explicitly consider biodiversity and ecosystem services in combination to avoid potential trade‐offs between the two and to ensure sustainable bioenergy production.